2022
DOI: 10.3390/antibiotics11081089
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Early Onset Sepsis (EOS) Calculator plus Universal Serial Physical Examination (SPE): A Prospective Two-Step Implementation of a Neonatal EOS Prevention Protocol for Reduction of Sepsis Workup and Antibiotic Treatment

Abstract: Current neonatal early-onset sepsis (EOS) guidelines lack consensus. Recent studies suggest three different options for EOS risk assessment among infants born ≥35 wks gestational age (GA), leading to different behaviors in the sepsis workup and antibiotic administration. A broad disparity in clinical practice is found in Neonatal Units, with a large number of non-infected newborns evaluated and treated for EOS. Broad spectrum antibiotics in early life may induce different short- and long-term adverse effects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…For late preterm and term infants, it has been shown repeatedly that implementation of a sepsis calculator could significantly reduce the proportion of newborns empirically treated with antibiotics. [29][30][31][32][33] For VLBWI, there is yet a lack of corresponding studies. Nonetheless, major efforts should be made to develop algorithms that could better predict the risk of EOS and help reduce antibiotic use also in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For late preterm and term infants, it has been shown repeatedly that implementation of a sepsis calculator could significantly reduce the proportion of newborns empirically treated with antibiotics. [29][30][31][32][33] For VLBWI, there is yet a lack of corresponding studies. Nonetheless, major efforts should be made to develop algorithms that could better predict the risk of EOS and help reduce antibiotic use also in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a growing body of evidence suggests that antibiotics in VLBWI can and should be managed more restrictively. For late preterm and term infants, it has been shown repeatedly that implementation of a sepsis calculator could significantly reduce the proportion of newborns empirically treated with antibiotics 29–33. For VLBWI, there is yet a lack of corresponding studies.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent further unnecessary antibiotic treatment, we advocate the need for a new screening strategy, possibly in the form of a value-based (multivariate) approach such as the EOS calculator in combination with a serial physical examination. 12…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic review and meta-analysis found that management guided by an early-onset sepsis calculator was associated with a significant reduction in empirical antibiotic therapy compared with conventional management, with a relative risk of 56% in before-after implementation studies. 11 Furthermore, Cavigioli et al 12 demonstrated that the combination of the neonatal EOS calculator and serial physical examinations can reduce the empirical antibiotic rate even more, to 1.4%. This illustrates that a categorical approach may be associated with unnecessary diagnostics and treatment and thus is not the best way to approach neonates and EOS risk.…”
Section: Discussionmentioning
confidence: 99%
“…It includes the combination of EOS calculator and SPE for all newborns with the possibility of evaluating the administration of antibiotic therapy in infants showing only mild respiratory symptoms with other systemic signs. Combined strategy seems to significantly reduce laboratory testing and antibiotic prescriptions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%